Modification of Cellulose by Esterification Crosslinking to Manipulate Its Microstructure for Enhanced Sodium Storage in Hard Carbon - Xingyun Zhang; Yue Hu; Yan Wang; Ming Li; Cuiying Lu; Shixiong Sun; Junwei Lang (Batteries)
The active hydroxyl group of cellulose plays a crucial role in regulating the microstructure of cellulose-derived hard carbon, which ultimately affects its sodium storage capacity. Through small-angle X-ray scattering (SAXS) and X-ray atomic pair distribution function (PDF) analysis, we proved that modification of cellulose by esterification crosslinking can introduce more closed pores into the carbonized hard carbon, which is beneficial for promoting sodium ion storage. Our results demonstrate that by optimizing the conditions used for esterification cross-linking modification, the sodium storage capacity of cellulose-derived hard carbon could be increased from 254 to 348 mAh g−1, with an increase in plateau capacity from 140 to 230 mAh g−1. This study makes a significant contribution towards establishing industrial applications for cellulose-derived hard carbon.